An Effective Epipolar Geometry Assisted Motion Estimation Technique for Multi-View Image and Video Coding - Lu, Jiangbo; Cai, Hua; Lou, Jian-Guang; Li, Jiang (International Conference on Image Processing, 2006)
To efficiently encode data-intensive multi-view imaging content, conventional hybrid predictive coding methodologies choose to address the compression by exploiting temporal and inter-viewpoint redundancy. However, their key yet time-consuming component, motion estimation (ME), is usually not efficient in inter-viewpoint prediction because inter-viewpoint motion is quite different from temporal motion. In essence, inter-viewpoint correlation is subject to epipolar geometry, which provides constraints for multi-view image sequences. A fast inter-viewpoint ME technique is hence proposed in this paper to accelerate the encoding by employing epipolar geometry. Theoretical analysis and experimental results prove that the proposed ME algorithm can greatly reduce search region and effectively track large and irregular motion that is typical for convergent multi-view camera setups. As a result, compared with fast full search at large search size adopted in H.264, our proposed ME algorithm can obtain a similar coding efficiency while achieving a speedup ratio of 2.9.